A vária máscara de Joana : melancolia em perto do coração selvagem - Portugal, Daniel da Silva (2007)
Entitled Joana s several mask: the melancholy in Perto do coração selvagem, the work is divided in six parts: the first one consists of the elaboration of a theoretical sketch about the melancholy that it offers the presuppositions that orientate the work, it is a short introduction about the study of the melancholy, a report until our time, the against-depressive ones and the arrival of the melancholy in Brazil and their particularities; the second part raises the theme of the melancholy, deepening its conception until what is called creative melancholy spread by Walter Benjamin, it serves as anchor for Clarice s writing and as a potential force for the processes lived by the characters of this writer; the third part examines Clarice Lispector s method emphasizing important points of production related to the theme of the melancholy, her style is the psychological analysis; the last one parts (fourth, fifth and sixth parts) are divided in topics that illustrate the conflicts, in most of the time contradictory, of the protagonist Joana, as well as, her difficult interaction with the things and the people that surround her. The fragmentary writing, the being's essential searches, the proximity with the death, the multiplicity of voices of feminine, De profundis, surrealist images, the incessant search for the thing , trips, epiphany, the flaw in the language, the taste of the badly, everything starting from melancholy - transformation and creation tool. The work about melancholy (Freud, Benjamin, Kristeva), it s place of ambiguous and contradictory movements. It is a trip that leads to several corporal and psychological sensations of Joana, enigma-scenes to be deciphered and conflicting images that make you wake up for a critical vision of the modern society. Since the beginning, something pulses without stopping, an incessant memory and the search for something that is lost. We are before recyclings of the interior/exterior, pain/pleasure, visions, abyss, ecstasy in the future and an exit through the melancholic light